2007
DOI: 10.1098/rstb.2006.1997
|View full text |Cite
|
Sign up to set email alerts
|

Dolphin social intelligence: complex alliance relationships in bottlenose dolphins and a consideration of selective environments for extreme brain size evolution in mammals

Abstract: Bottlenose dolphins in Shark Bay, Australia, live in a large, unbounded society with a fission-fusion grouping pattern. Potential cognitive demands include the need to develop social strategies involving the recognition of a large number of individuals and their relationships with others. Patterns of alliance affiliation among males may be more complex than are currently known for any non-human, with individuals participating in 2-3 levels of shifting alliances. Males mediate alliance relationships with gentle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
229
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(235 citation statements)
references
References 116 publications
2
229
1
1
Order By: Relevance
“…Research has shown that ecological variables, such as social environment (Connor, 2007; Kotrschal, Rogell, Maklakov, & Kolm, 2012a; Shultz & Dunbar, 2006b), diet (Allen & Kay, 2012; Shultz & Dunbar, 2006a), habitat (Crispo & Chapman, 2010; Gonda et al., 2009b; Kotrschal, Sundstrom, Brelin, Devlin, & Kolm, 2012b), and predators (Gonda et al., 2009a,b, 2011; Walsh et al., 2016), play an important role in brain size plasticity and brain size evolution (see also Gonda, Herczeg, & Merila, 2013). These latter studies exploring the connection between predators and selection on brain size have largely compared populations where adults are susceptible to predators (Gonda et al., 2009a,b, 2011; Walsh et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that ecological variables, such as social environment (Connor, 2007; Kotrschal, Rogell, Maklakov, & Kolm, 2012a; Shultz & Dunbar, 2006b), diet (Allen & Kay, 2012; Shultz & Dunbar, 2006a), habitat (Crispo & Chapman, 2010; Gonda et al., 2009b; Kotrschal, Sundstrom, Brelin, Devlin, & Kolm, 2012b), and predators (Gonda et al., 2009a,b, 2011; Walsh et al., 2016), play an important role in brain size plasticity and brain size evolution (see also Gonda, Herczeg, & Merila, 2013). These latter studies exploring the connection between predators and selection on brain size have largely compared populations where adults are susceptible to predators (Gonda et al., 2009a,b, 2011; Walsh et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The capacity to recognize who outranks whom, who is closely bonded with whom, who is likely to support whom or intervene against whom, and to adjust one's behaviour accordingly has been documented in apes (e.g. Tomasello and Call 1997;De Waal 2007), Old World (Cheney et al 1986;Cheney and Seyfarth 1999), New World monkeys (Perry et al 2004; but see also Ferreira et al 2006), other mammals (Engh et al 2005;Connor 2007;Johnson 2010) and in birds (Peake et al 2002;Seed et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…We now know that these biological preconditions are not exclusive to primates and have been demonstrated in many social mammals, such as elephants (McComb 2001), hyenas (Holekamp et al 2007) and cetaceans (Connor 2007). What about birds?…”
Section: The Avian Social Brain?mentioning
confidence: 99%
“…Although there appears to be a clear relationship between social group size and brain (i.e. neocortex) size within primates (Dunbar 1992), carnivores, insectivores (Dunbar & Bever 1998), bats (Barton & Dunbar 1997) and cetaceans (Marino 2002;Connor 2007), no such relationship exists within another mammalian order, ungulates (Shultz & Dunbar 2006). Although the brain size analyses presented later in the paper were performed at the class rather than family level, it should be kept in mind that such analyses have yet to be performed in mammals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation